Understanding the Reinforcing Mechanisms in Kenaf Fiber/PLA and Kenaf Fiber/PP Composites: A Comparative Study - Seong Ok Han; Mehdi Karevan; I. Na Sim; Md A. Bhuiyan; Young Hun Jang; Jonathan Ghaffar; Kyriaki Kalaitzidou (International Journal of Polymer Science)
This study focused on exploring the feasibility of green composites made from biodegradable and renewable materials as potential alternatives to petroleum polymer composites and understanding the reinforcing mechanisms in composites containing kenaf fibers (KF). KF-reinforced poly(lactide) acid (PLA) composites were made using melt compounding and injection molding, and their properties were compared to that of KF-reinforced polypropylene (PP) composites. The flexural properties and thermomechanical behavior were determined as a function of the fiber content, the crystallization of PLA and PP was studied using X-ray diffraction and differential scanning calorimetry, and the composites’ morphology was investigated using scanning electron microscopy. It was concluded that PLA exhibits higher modulus and Tg compared to those of neat PP. The modulus of the composites at 40 wt% fibers is 6.64 GPa and 2.96 GPa for PLA and PP, respectively. In general, addition of kenaf results in larger property enhancement in PP due to better wetting of the fibers by the low melt viscosity PP and the crystallization behavior of PP that is significantly altered by the fibers. The novelty of this work is that it provides one-to-one comparison of PLA and PP composites, and it explores the feasibility of fabricating green composites with enhanced properties using a simple scalable process.